Relationship between perioperative oncological evaluation and recurrence using circulating tumor DNA with KRAS mutation in patients with colorectal cancer. (21st March 2022) - Hayashi, Takaomi; Yoshida, Yoichiro; Yamada, Teppei; Tanaka, Keita; Shimaoka, Hideki; Kajitani, Ryuji; Munechika, Taro; Nagano, Hideki; Matsumoto, Yoshiko; Komono, Akira; Sakamoto, Ryohei; Aisu, Naoya; et al.
Abstract: Background: The detection of circulating tumor DNA (ctDNA) in colorectal cancer (CRC) by liquid biopsy may have prognostic information. In this perioperative study, we evaluate if there is a relationship between mutant allele frequency (MAF) of Kirsten rat sarcoma viral oncogene homolog ( KRAS ) and tumor recurrence and how that could be useful in the early detection of recurrence. Methods: Among 304 cases of colorectal cancer surgery, ctDNA was sampled from the perioperative blood of 84 patients with CRC with KRAS mutation (exon 4 p.A146T, exon 4 p.A146V, exon 2 p.G12A, exon 2 p.G12C, exon 2 p.G12D, exon 2 p.G12S, exon 2 p.G12V, exon 2 p.G13D, exon 3 p.Q61H) and analyzed using the digital polymerase chain reaction system. The median observation period was 26 months. Results: Although the relationship between the perioperative MAF of KRAS and recurrence was not proved, tumor diameter, tumor depth, and stage were correlated with the preoperative MAF of KRAS ( p  = 0.034, p  = 0.002, p  = 0.008). However, tumor diameter, tumor depth, and stage did not correlate with MAF of KRAS at postoperative day 30. Conclusions: In this study, pathological tumor size, tumor depth, and stage were correlated with preoperative MAF of KRAS, but it was unreliable to predict recurrence by detection of ctDNA with KRAS mutation in the perioperative period of colorectal surgery. Abstract : In this study, pathological tumor size, tumor depth, and stage were correlated with preoperative MAF of KRAS, but it was unreliable to predict recurrence by detection of ctDNA with KRAS mutation in the perioperative period of colorectal surgery.